Sunitinib in patients with chemotherapy-refractory thymoma and thymic carcinoma: an open-label phase 2 trial. Issue 2 (February 2015) - Thomas, Anish; Rajan, Arun; Berman, Arlene; Tomita, Yusuke; Brzezniak, Christina; Lee, Min-Jung; Lee, Sunmin; Ling, Alexander; Spittler, Aaron J; Carter, Corey A; Guha, Udayan; Wang, Yisong; et al.
Summary Background No standard treatments are available for advanced thymic epithelial tumours after failure of platinum-based chemotherapy. We investigated the activity of sunitinib, an orally administered tyrosine kinase inhibitor. Methods Between May 15, 2012, and Oct 2, 2013, we did an open-label phase 2 trial in patients with histologically confirmed chemotherapy-refractory thymic epithelial tumours. Patients were eligible if they had disease progression after at least one previous regimen of platinum-containing chemotherapy, an Eastern Cooperative Oncology Group performance status of two or lower, measurable disease, and adequate organ function. Patients received 50 mg of sunitinib orally once a day, in 6-week cycles (ie, 4 weeks of treatment followed by 2 weeks without treatment), until tumour progression or unacceptable toxic effects arose. The primary endpoint was investigator-assessed best tumour response at any point, which we analysed separately in thymoma and thymic carcinoma cohorts. Patients who had received at least one cycle of treatment and had their disease reassessed were included in the analyses of response. The trial was registered with ClinicalTrials.gov, number NCT01621568. Findings 41 patients were enrolled, 25 with thymic carcinoma and 16 with thymoma. One patient with thymic carcinoma was deemed ineligible after enrolment and did not receive protocol treatment. Of patients who received treatment, one individual with thymic carcinoma was not assessable because she died. Median follow-up on trial was 17 months (IQR 14·0–18·4). Of 23 assessable patients with thymic carcinoma, six (26%, 90% CI 12·1–45·3, 95% CI 10·2–48·4) had partial responses, 15 (65%, 95% CI 42·7–83·6) achieved stable disease, and two (9%, 1·1–28·0) had progressive disease. Of 16 patients with thymoma, one (6%, 95% CI 0·2–30·2) had a partial response, 12 (75%, 47·6–92·7) had stable disease, and three (19%, 4·1–45·7) had progressive disease. The most common grade 3 and 4 treatment-related adverse events were lymphocytopenia (eight [20%] of 40 patients), fatigue (eight [20%]), and oral mucositis (eight [20%]). Five (13%) patients had decreases in left-ventricular ejection fraction, of which three (8%) were grade 3 events. Three (8%) patients died during treatment, including one individual who died of cardiac arrest that was possibly treatment-related. Interpretation Sunitinib is active in previously treated patients with thymic carcinoma. Further studies are needed to identify potential biomarkers of activity. Funding National Cancer Institute (Cancer Therapy Evaluation Program).